New correlation for predicting asphaltene deposition - Sulaimon, A.A. (Society of Petroleum Engineers, 2015)
Precipitation and deposition of hydrocarbon solids such as asphaltenes and wax are some of the major challenges facing the oil and gas processing and transportation industry. Deep-water, high pressure and high temperature (HPHT) environment are currently being explored for meeting the ever increasing energy demand and operating companies allocate huge resources annually to mitigate flow assurance problems. The aim of this study was to develop correlations for predicting asphaltene deposition tendency of crude oils since the experimental analyses are both laborious and capital intensive. SARA analyses and refractive index measurements were conducted on four Malaysian crude oil samples and the correlation development is based on the measured Collodal Instability Index (CII), the Refractive Index (RI), molecular weight of oil and the molecular weight of the lumped fraction of the crude oil. Results from the mathematical correlations developed from the experimental data have proved reliable as predictions compare favourably well with the actual data. Analysis of the results show that the difference between the refractive index (RI) of the crude oil and the refractive index at the onset of asphaltene precipitation for the samples (ARI) are less than 0.045 while the CII for the four crude oil samples A, B, C, and D are 1.09, 1.43, 5.64 and 5.83 respectively. These indicate that all the oils investigated have high tendency to precipitate asphaltene. Copyright 2015, Society of Petroleum Engineers.